Ayurvedic Management of Emesis Gravidarum - A Case Report - Shahina Mole S,; Deepa C R, (International Journal of Ayurveda and Pharma Research, 2022)
Emesis is a common experience in first trimester of pregnancy affecting 70 to 80% of all pregnant women. Altered immunological endocrinological and psychological states are responsible for initiation of symptoms. Mild to moderate emesis gravidarum have a significant adverse effect on quality of women's life. Even though onset is physiological its morbidity has to be reduced to minimize disease burden, enhance maternal health and to prevent hyper emesis gravidarum. Anti-emetic and anti-histamines are used in conventional Allopathic practice. Ayurvedic principle is early intervention and prevention of hyperemesis gravidarum with lifestyle modifications and adopting Pathya ahara. This is a case report of emesis gravidarum managed with pharmaco nutrient product –Malarinji modaka